Prevalence of diabetes among homeless men in Nagoya, Japan: A survey study - Yamamoto, Mayumi (J Diabetes Investig, 2018)
AIMS/INTRODUCTION: The diabetes status of homeless people has not been elucidated because of the limited access to this population. We carried out a survey of the prevalence of diabetes and prediabetes among homeless men in Nagoya, Japan, and assessed the associations between diabetes prevalence and sociodemographic characteristics. MATERIALS AND METHODS: Interviews relating to individuals’ sociodemographic background, mental illness and cognitive ability, and blood sampling were carried out for 106 homeless men (mean age 54.2 ± 12.7 years). Diabetes, prediabetes and normoglycemia were diagnosed according to the individual's hemoglobin A1c level: ≥6.5%, 6.4–6.0% and ≤5.9%, respectively. Mental illness and cognitive disability were diagnosed using the Mini‐International Neuropsychiatric Interview and Wechsler Adult Intelligence Scale‐III, respectively. Associations between the prevalence of diabetes/prediabetes and mental illness/cognitive disability or sociodemographic background were analyzed using the χ(2)‐test. RESULTS: Seven (6.6%) and 12 (11.3%) participants were diagnosed as having diabetes and prediabetes, respectively, which was a similar trend to that of general populations in Japan National Health and Nutrition Survey data. There was a significant difference in the prediabetes prevalence between groups with and without a history of having social support; however, no significant associations were found between the diabetes/prediabetes prevalence and mental illness/cognitive ability or participants’ sociodemographic background. CONCLUSIONS: The incidence of diabetes in Japanese homeless men was similar to that in the general population, and the prediabetes incidence was lower in the group with social support than in that without. Early intervention for preventing diabetes and social support that focuses on diabetes management is important for homeless people.